2011
DOI: 10.1590/s0074-02762011000700006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of mefloquine and praziquantel combination therapy in mice harbouring juvenile and adult Schistosoma mansoni

Abstract: Praziquantel (PZQ) is currently the only drug widely used for the treatment of schistosomiasis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…The major cause of metabolic dysfunction during pathogenesis is the site specific oxidative damage of some of the susceptible amino acids of protein (Bandopadhyay et al, 1999). In accord with the studies of El-Emam et al (2011), El-Lakkany et al (2011) and Abdel-Fattah and Ahmed (2011 the present study showed that S. mansoni infection in mice induced a significant decrease in the serum total protein. In consonance with the report of El-Lakkany et al (2011) andAbdelFattah andAhmed (2011), data from the present study showed that treatment with Mef at the two tested doses for juvenile and adult stages significantly increased the level of total protein activities in infected-treated group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The major cause of metabolic dysfunction during pathogenesis is the site specific oxidative damage of some of the susceptible amino acids of protein (Bandopadhyay et al, 1999). In accord with the studies of El-Emam et al (2011), El-Lakkany et al (2011) and Abdel-Fattah and Ahmed (2011 the present study showed that S. mansoni infection in mice induced a significant decrease in the serum total protein. In consonance with the report of El-Lakkany et al (2011) andAbdelFattah andAhmed (2011), data from the present study showed that treatment with Mef at the two tested doses for juvenile and adult stages significantly increased the level of total protein activities in infected-treated group.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, there is an urgent need to develop a new antischistosomal drug. The antimalarial drug mefloquine (Mef) possesses interesting antischistosomal properties (El-Lakkany et al, 2011;Xiao, 2013). The treatment was recommended in several studies as it provided many complementary goals, a reduction of egg-induced pathology, minimal parenchymal changes and the eradication of worms (El-Lakkany et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] Finally, experimental studies have shown the anti-malarial drug mefloquine to be efficacious against juvenile and adult parasites from the three main schistosome species affecting man. Mefloquine has also been shown to act synergistically with PZQ, as combination therapy, against schistosomes in experimental studies, [27] but this effect could not be reproduced in recent human trials of people infected with S. haematobium parasites. [28] Combination therapy has the advantage of delaying/averting the development of drug resistance parasites when the drugs have different pharmacokinetcis.…”
mentioning
confidence: 99%